2016
DOI: 10.31436/ijes.v4i1.80
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Concept-Mapping on Secondary School Students’ Performance in Islamic Studies

Abstract: This study examined the effect of concept-mapping instructional method on secondary school students’ performance in Islamic Studies in Oyo State, Nigeria. The study employed a pre-test, post-test control group, quasi-experimental design. The sample comprised Senior Secondary School class 2 (SSS 2) students purposively drawn from three secondary schools in Oyo State. The students in experimental and control groups were in their normal classroom setting (intact classes) and were not reorganized. Experimental gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It further indicates that the factor on the quality of teachers has a significant effect on pupils' academic performance as perceived by the young ones aged 10. This is supported by the study of Ajidagba, et al (2018) found that teachers' quality have a significant relationship with pupils' academic performance. Similarly, factors on home environment and learning environment were also perceived by the matured pupils' those aged of 13 can also affect their academic performance.…”
Section: Correlation Between the Academic Performance Of Pupils And T...mentioning
confidence: 66%
“…It further indicates that the factor on the quality of teachers has a significant effect on pupils' academic performance as perceived by the young ones aged 10. This is supported by the study of Ajidagba, et al (2018) found that teachers' quality have a significant relationship with pupils' academic performance. Similarly, factors on home environment and learning environment were also perceived by the matured pupils' those aged of 13 can also affect their academic performance.…”
Section: Correlation Between the Academic Performance Of Pupils And T...mentioning
confidence: 66%